Traces of the Presence of the Argonauts in the Imaginarium of Slovenian Culture - Gruda, Marlena (Poznańskie Studia Slawistyczne, 2024)
The myth of the Argonauts, well-known in Greek mythology, has made its mark in the consciousness of the Slovenians as an important element indicating the connection of Slovenian culture with ancient culture. The basis for the following thesis is the assumption of the so-called Danubian version of the myth according to which the Argonauts, returning from the Black Sea (Colchis in Georgia), visited the territory of present-day Slovenia and founded the city of Emona. The incorporation of this version in the epic poem of Apollonius of Rhodes has increased the interest among researchers of the history of Ljubljana as well as inspired artists to reinterpret the voyage of the Argonauts in culture. The aim of this work is to explore the traces of the Argonauts’ presence in the imaginary memory of Slovenes in Slovenian literature, taking into regard the status and functioning of the Argonauts myth in the literary and non-literary reality of Slovenia.